Construction of as prototype D-Statcom for voltage sag mitigation - Mariun, Norman; Masdi, Hendri; Bashi, S. M.; Mohamed, A.; Yusuf, Sallehhudin (EuroJournals, 2009)
This paper presents the design of a prototype distribution static compensator (D-STATCOM) for load compensation in an unbalanced distribution system. The DSTATCOM is intended to replace the widely used static Var compensator (SVC). The compensation scheme of the DSTATCOM is derived using the symmetrical component method.In this work, the 12-pulse D-STATCOM configuration with IGBT has been designed and the graphic based models of the DSTATCOM have been developed using the PSCAD/EMTDC electromagnetic transient simulation program. Accordingly,simulation is first carried out to illustrate the use of DSTATCOM in mitigating voltage sag in a distribution system. The D-STATCOM has been developed using DSP controller to achieve excellent overall performance. Simulation results prove that the D-STATCOM is capable of mitigating voltage sag by controlling PWM of the system using DSP board.